Mature Teratoma Combined with Bladder Stones: A Case Report and Literature Review - Li A; Wang X; Wang C; Song Q; Niu Y; Wang P; Yue J (Research and Reports in Urology)
Anan Li,1 Xiaobo Wang,2 Chang Wang,2 Qingling Song,3 Yanbin Niu,1 Peng Wang,4 Juntao Yue5 1Department of Urology, 985th Hospital of People’s Liberation Army Joint Logistic Support Force, Taiyuan, Shanxi, People’s Republic of China; 2Department of Gastroenterology, 985th Hospital of People’s Liberation Army Joint Logistic Support Force, Taiyuan, Shanxi, People’s Republic of China; 3Department of Laboratory and Pathology, Lintong Rehabilitation Center of Joint Logistics Support Force of People’s Liberation Army, Lintong, Shaanxi, People’s Republic of China; 4Department of Pathology, 985th Hospital of People’s Liberation Army Joint Logistic Support Force, Taiyuan, Shanxi, People’s Republic of China; 5Reproductive Andrology and Human Sperm Bank, Key Laboratory of Obstetric, Gynecologic and Pediatric Diseases and Birth Defects of Ministry of Education, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Juntao Yue, Reproductive Andrology and Human Sperm Bank, Key Laboratory of Obstetric, Gynecologic and Pediatric Diseases and Birth Defects of Ministry of Education, West China Second University Hospital, Sichuan University, No. 1416 Chenglong Avenue, Jinjiang District, Chengdu, Sichuan, People’s Republic of China, Tel +86 02888570175, Email 2622958466@qq.comAbstract: Teratoma is neoplasia originating from a germ cell, which usually contains identifiable tissue derived from all three germ cell layers. The presence of teratoma is due to an organ being affected by a tumor, which generally occurs in ovary. Teratoma is also seen occasionally in some extragonadal organs. However, a primary teratoma in the bladder is a rare entity. We hereby present a case of bladder teratoma. A 53-year-old woman whose chief complaints were urinary interruption, pilimiction, and a stone in her urine was diagnosed by cystoscopy and received rehabilitation after tumor resection surgery. She was then symptom-free and further follow-up observation was in progress. We also include a literature review concerning primary bladder teratoma.Keywords: mature teratoma, dermoid cyst, bladder tumor